IMPLEMENTASI PRINSIP KEDAULATAN RAKYAT DALAM SISTEM HUKUM DAN KONSTITUSI INDONESIA - Dimas Satria Hemarnaswa; Tomson Situmeang (Honeste Vivere, 2026)
This article examines the implementation of the principle of popular sovereignty within Indonesia’s legal and constitutional system. Although the 1945 Constitution affirms that sovereignty resides in the people, its realization in state governance remains inconsistent. The purpose of this article is to analyze the constitutional regulation of popular sovereignty and to assess its implementation in practice. This research employs a normative juridical method using statutory and conceptual approaches. The findings show that popular sovereignty in Indonesia is strongly established at the normative level; however, its implementation tends to be procedural rather than substantive. Electoral processes, political representation, and law-making practices do not always reflect the genuine will of the people due to limited political competition, weak representative institutions, and insufficient public participation. In addition, while the Constitutional Court plays an important role in safeguarding constitutional principles, its effectiveness depends on institutional integrity and consistent enforcement. Therefore, strengthening popular sovereignty requires improving the quality of elections, enhancing representative functions, and ensuring meaningful public participation in governance.